Hydroxyapatite (ha) Scaffold Supplemented With Vegf And Bmp-2 Growth Factors Enhanced Osteogenic Proliferation And Differentiation Of Mc3t3-e1 Cells - Musa Intan Maslina; Abdullah Amira Raudhah (Pharmacy Education Journal, 2024)
Indexed by Scopus